Parasite fauna of Epinephelus coioides (Hamilton, 1822) (Epinephelidae) as environmental indicator under heavily polluted conditions in Jakarta Bay, Indonesia. Issue 2 (30th September 2016) - Neubert, Kilian; Yulianto, Irfan; Theisen, Stefan; Kleinertz, Sonja; Palm, Harry W.
Abstract: The objective of this study was to assess the environmental conditions of a heavily polluted marine habitat using descriptors of fish parasites. Epinephelus coioides from Jakarta Bay as well as off Jakarta Bay was studied for metazoan parasites. Based on 70 fish and considering previous studies (230 fish), an environmental indicator system was designed. Including the recent study, a total of 51 parasite species have been recorded for E. coioides in Indonesian waters. Seven of them combined with five parasitological indices are useful descriptors for the environmental status of marine ecosystems. The results are visualized in a star graph. A significant different parasite infection between nine analyzed localities demonstrates the negative influence of the megacity Jakarta onto the coastal environment. We herewith complete a parasite based indicator system for Indonesian coastal waters, and suggest that it can be used in other marine habitats as well as for further epinephelids. Highlights: A fish parasite based indicator system for environmental conditions of coastal Indonesian ecosystems is proposed. The system relies on altered parasitological descriptors of Epinephelus coioides in different anthropogenic affected areas. Jakarta Bay is revealed as most seriously affected locality. The developed system indicates to what level all other sampled localities are impacted.